(untitled) (Acta Scientiarum. Health Sciences, 2013)
Gastro-resistant capsules are often used for several purposes, such as protection of unstable drugs in acid medium to the action of gastric fluids or protection of the gastric mucosa to irritants drugs. The aim of this study was to verify the variation of preparations of capsules coating with cellulose acetate phthalate and methacrylic acid copolymer, without drug addition, in 7-10% coating concentrations, prepared manually with four or five immersions in tested coating solution. Results were analyzed considering the formulation’s disintegration test. Within the context of formulations under analysis, it was observed that the capsules coated with cellulose acetate phthalate 10% complied with the pharmacopeia’s disintegration specifications. However, capsules coated with methacrylic acid copolymer did not show accordance with the pharmacopeia’s specifications. The results emphasize the need for the standardization of coating methodology.